Islam, Democracy, and Cosmopolitanism - Amr G. E. Sabet (International Institute of Islamic Thought, 2015)
Ali Mirsepassi and Tadd Graham Fernée introduce their book as a “critical study of citizenship, state, and globalization in societies historically influenced by Islamic traditions and institutions” (p. 1). They place their approach in the framework of the relationships between individuals and the state, religion, and political community as part of investigating the democratic aspirations of Islamic societies. These relationships are then contextualized in a global setting wherein such aspirations presumably interconnect with some “cosmopolitan ideal.” The book’s main thrust is quite clear from the outset in light of the authors’ two grounding assumptions: In order to attain agency and freedom humanity in general, but Muslims in particular, must (1) respect the “core Enlightenment values” of human equality and dignity regardless of ethnicity, religious affiliation, and belief or disbelief and (2) acquire a spatial vision of democracy that incorporates “the cognitive-imaginative resources of a multidimensional Islamic heritage” (p. 1). In short, an approach in which an overarching and universal Eurocentric value structure that respects Islam would help deconstruct any essentialist framework that posits the latter and Enlightenment as dichotomous opposites. This could be done through a “global ethic of reconciliation” – an alternative to the “death of epistemic universalism” (p. 30) along John Stuart Mill’s depiction of barbarian races in their failed relations to liberty – that sociologically interconnects three domains of a specific spatial-temporal context of Islamic practices, the democratic social virtue of nonviolence, and the cosmopolitanism of universal and shared human values (p. 4). The authors’ analytical framework integrates three strands of twentiethcentury critical thought concerning democratic nation-building. These pertain to John Dewey’s “conceptual pluralism,” Edmund Husserl’s “lifeworld” and “temporal Horizons,” and Amartya Sen’s conception of cultural variability and freedom as “capabilities” (p. 5). This is articulated within what Mirsepassi and Fernée designate as a “Pragmatic Revolution” that perceives an “unthought conjuncture between the Jasmine Revolution” – the so-called Arab Spring – and these critical strands’ gaining ground in western thought (p. 3). This is done through the tripartite problematic of “embededness,” “embodiment,” and the “unthought” (p. 7), all of which point to a new, even if inadequately, “theorized cosmopolitan horizon” (p. 7). The goal is to understand the “Jasmine Revolutions” as new popular forms of mobilization that respond to a specific pattern of the modern experience, while asking the question of ...